THE PORTRAYAL OF CRIMINALITY AS SEEN IN EDGAR JEPSON AND MAURICE LEBLANC’S ARSENE LUPIN - -, Hilaria Dewi Hapsari (Conscientia - Journal on Language, Literature, and Culture, 2024)
This research analyzes the portrayal of criminality as seen in the novel Arsène Lupin by Edgar Jepson and Maurice Leblanc. The purpose of this research is to find out the forms of crimes that are depicted in the novel, how the crimes in the novel are carried out, and how the crimes are revealed in the novel Arsène Lupin. The method of collecting data used in this research is library research and the method of analyzing data used in this research is descriptive qualitative. The researchers use objective approach and several theories such as the types of crimes, cost-benefit analysis, the theory of criminal act, and crime scene investigation to analyze the data. From the results of the data analysis, the researcher finds that the forms of crime are burglary and theft. The crimes in the novel are carried out through a series of criminal acts that consist of hiding documents, disguising, warning the target, leaving a trace, baffling people, and elaborating crime schemes. Last, the crimes in the novel are revealed through the examination of Victoire and the examination of the Duke of Charmerace.